(untitled) - Jordan, William R. (Washington, 2011)
Making Nature Whole is a seminal volume that presents an in-depth history of the field of ecological restoration as it has developed in the United States over the last three decades. The authors draw from both published and unpublished sources, including archival materials and oral histories from early practitioners, to explore the development of the field and its importance to environmental management as well as to the larger environmental movement and our understanding of the world.
Keywords: Restoration ecology,Sinh thái phục hồi,Natural resources,Nguồn tài nguyên thiên nhiên